Biblioteca como infraestrutura de apoio para a Educação a Distância - Ferreira, Ligia Leite Castelli (Universidade Federal de São Carlos, 2018)
The problem of research investigated comes in a critical aspect related to distance education, the development of research by distance mode students. Whereas higher education values by teaching, research and extension, argues that the library is one of the main support equipment to increase of this triad. Thus, the general objective of this research is to analyze and discuss the role of the library as infrastructure to support distance education. The specific objectives are: to describe the panorama of distance education in Brazil, highlighting the guidelines of the Ministry of Education for the operation of this equipment, in the context of distance education at the Federal University of São Carlos; characterize and discuss the University Library and your action potential in distance education; systematize and present the research overview in EaD, analyze the situation of construction and use of information hubs with interest in the chacarterization of the libraries of the poles; analyze Community Library products and services of the Federal University of São Carlos to discuss the existence or no of items developed specifically for these audiences and, finally, an analysis and discussion of the results. In order to operationalize the study were used the following methodological procedures: literature review on EaD in Brazil and documentar research on governamental sites; bibliographical research and subject analysis on library Science and related fields; systematic review of 749 abstracts published in proceedings of the International Symposium on distance education (SIED) from 2012, 2014 and 2016; a systematic review of the literature in Data Bases in Information Science and Education; documentary analysis of reports produced by the Foundation of institutional support to the Scientific and Technological Development of the UFSCar, available online; analysis of online government documents and analysis of the interface of the Community Library of UFSCar; analysis and discussion of the results found with the research work shows that the format of the distance in Brazil leads to weaknesses in the planning of the physical infrastructure of library, which is reflected in the quality of services offered; systematic review of SIED shows only 4 scientific articles on the theme library and distance education a total of 749 scientific articles; the theme library and distance education in Information Science and related areas reveal 45 articles. Finally, authors that deepen the theme library and distance education comprise the library as a pedagogic resource while the Brazilian government documents to describe how physical infrastructure, a mismatch. And, the university library is represented by the UFSCar Community Library offers online services in data bases via proxy for remote users. The conclusion is that the library role have not been captured in the Brazilian universe of distance education, it is not well established. Although the library's contribution opportunities for distance education in terms of physical structure materials and insertion in the teaching learning process there is still no formal action of University Library institutionalized involved in public distance higher education actions.
Library as a support infrastructure for Distance Education
Keywords: Biblioteca para EaD; Ensino Superior a Distância; Biblioteca a distância; Distance education; Library; University library; Community library; Higher education; CIENCIAS SOCIAIS APLICADAS